Implementation of “Smart” Solutions and An Attempt to Measure Them: A Case Study of Czestochowa, Poland - Biadacz, Renata; Biadacz, Marek (Energies (Basel), 2021)
The aim of the study is to present the implemented “smart” solutions and the developed indicators of their measurement in the context of the city of Częstochowa (Poland), as well as a participant in the “Benchmarking—we are looking for the best smart city solutions”. In order to achieve the assumed goal, a traditional review of the literature on the subject in the field of “smart city” was carried out. Then, the methodological assumptions related to developing a model set of indicators for cities participating in the program have been presented. In addition, a comparative analysis of the obtained indicators values for cities, Częstochowa and Bydgoszcz, has been carried out in the scope of one exemplary measure. The proposed research procedure can be used to analyze and evaluate cities in the country, as well as to select alternative solutions in the context of other urban features. Due to the fact that other cities in Poland will also participate in the study, the significance of this work will have a wide impact. The research presented in the article is only a part of an intended larger initiative in which several dozen Polish cities will take part.